Riqueza, distribución y conservación de los topos y las musarañas (Mammalia, Eulipotyphla) de México - Lázaro Guevara (Therya, 2015)
Introduction. Moles (Talpidae) and shrews (Soricidae) are the only representatives of the order Eulipotyphla in Mexico and they account for 7% of mammals in the country. Despite their richness, even basic aspects such as their species-level taxonomic knowledge and geographical distribution are still uncertain. The scarcity of such information implies that the biology and conservation status of eulipotyphlans are also unclear or unevaluated, which involves a serious impediment to the design of management strategies for a group that tends to be susceptible to climate change and impacts of anthropogenic habitat transformation. Here, we performed a comprehensive assessment of the current state of knowledge and threats to the survival of Mexican moles and shrews using information from natural history collections and spatial environmental data. Methods. We reviewed the available information in biological collections (Table 1), databases, and literature records of Mexican eulipotyphlans, and explored the historical bias in the collection of their specimens through time and space (Fig. 1). The potential distribution was estimated for nearly all moles and shrews recorded in Mexico, using ecological niche modeling. Finally, we calculated the extent of potential distribution for each species within protected areas and within the most threatened ecosystems in Mexico to identify the most vulnerable taxa. Results. The eulipotyphlan diversity of Mexico is represented by 3 species of moles and 36 of shrews. Of all these, 26 species (67%) are endemic to the country and 27 (69%) are listed in a risk category by Mexican government or global assessments (Table 2). Eleven taxa are known only from no more ten specimens or from very few collecting sites. The shrew Sorex stizodon has not been recorded for more than a century. Potential distributions of nine species were not estimated because they are represented by just a few locality records (< 5 localities). Potential distributions of eulipothyphlans cover 69% of Mexican territory, but only 10.4% is located in protected areas and 77% of taxa have suitable habitat within tropical evergreen forest and cloud forest, the most threatened ecosystems in the country (Tables 2-3; Figs. 2-4). Discussion and conclusions. This paper provides the first detailed documentation of available information on the taxonomy, nomenclature, distribution, and threats of moles and shrews in Mexico. Information from natural history collections corroborates the sparse and biased knowledge about the actual distribution of eulipotyphlans (Ramírez-Pulido et al. 2005; Carraway 2007). Our spatial analyses provide evidence that several species may be more endangered than suggested by global approaches (IUCN) and Mexican government legislation. Several species of moles and shrews may be represented sparsely in collections because of insufficient collecting. Our niche models projected onto a map to identify potential distribution areas should be used